PERAN KOMITE MADRASAH DAN KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM - Manshur, Ahmad (At-Tuhfah : Jurnal Studi Keislaman, 2017)
“The relationship of madrasah with society is essentially a very instrumental in fostering and developing personal growth of learners in madrasah, in this case madrasah as a social system is an integral part of the larger system of society. On the other hand, madrasah should support the achievement of community goals, especially education needs. Therefore, madrasah should also know clearly what the needs and circumstances of society, especially against madrasah. The cause of the low quality of education in Indonesia certainly can not be separated from the role and leadership of a teacher as top leadernya. The madrasah committee has an important role as a giver of balance, support, control, and as a mediator between government and society in educational units. Head of madrasah as top leader in Islamic education institution hence head of madrasah of course have role of strategy in influencing all stakeholder of madrasah to reach goal of education of Islam. Together the madrasah committee and the head of madrasah in improving the quality of Islamic education in madrasah.”